Ethics ≠ Aesthetics. Issue 2 (4th May 2018) - Treib, Marc
Abstract: The resistance to a broad adoption of responsible landscape design derives in part from the confusion of ethics with aesthetics, that is, equating moral values with beauty—a conflation that hampers the pursuit of a beautiful expression for sustainable landscapes. Beauty results not from ethics, but instead from a skilful interweaving of form, space, proportion, light, and colour, the embrace of seasonal change, growth, a knowledge of vegetation, and a host of other natural processes. Stressing performance or ethics alone abrogates the landscape architect's responsibility to design truly appealing landscapes. A potential vehicle for achieving both ethical and aesthetically engaging landscapes is the Japanese mixing of formalities— shin-gyo-so (formal, semiformal, informal)—not by simple juxtaposition, but instead by entwining and embedding one within the other. Having high morals is laudable yet insufficient; one must know a language in order to write poetry.